OPTIMALISASI PEMBELAJARAN TEMATIK BERBASIS EXPERIENTIAL LEARNING UNTUK MADRASAH IBTIDAIYAH - Atikah Syamsi (Al Ibtida: Jurnal Pendidikan Guru MI, 2014)
ABSTRACTAmong alternative learning can be used to answer one of the problems in education related to the learning experience is to use the model of experiential learning that is almost similar to a scientific approach in thematic learning . Where thematic learning is more emphasis on the application of the concept of learning by doing something ( learning by doing ) . Therefore , teachers need to package or design a learning experience that would affect the significance of student learning. Learning experiences that demonstrate this relationship conceptual elements make the learning process more effective. Conceptual connection between subjects studied and will form the scheme , so that students will acquire knowledge of the unity and unanimity . Additionally , with the implementation of thematic learning in elementary school will help students , because according to the stage of development of students who still see everything as a whole (holistic).This research is a field (field research) is research by going directly to research places to observe and engage directly with the object of research . Type of research is qualitative research with inductive logic thinking . Sources of data in the study is the subject of where the data was obtained , the determination of the data is obtained by applying the population , meaning that the entire party in the role of research as a research target . Given in this study used a qualitative approach , the data analysis starts from the ground by using descriptive analytic method that is compiled by describing , interpreting data and analyzing all the things that are the focus of this researchKeywords : Experiential Learning, Thematic Learning,Â  Elementary School